Multidimensional analysis of factors affecting changes in population of people in the European Union states in terms of social security in Poland - Kozicki, Bartosz; Sowa, Bogdan; Tomaszewski, Jarosłąw (Polityka i Społeczeństwo, 2024)
The multidimensional comparative analysis of factors influencing the change in the human population in selected European countries in terms of social security in Poland was conducted in the study., the highest population growth between 2013-2022 out of 31 European countries analyzed was recorded in Germany (2 713 378), France (2 271 575) and Sweden (896 433). During that period, a decrease of 408 288 people was recorded in Poland. The main factors influencing changes, especially population declines, include the negative difference between human births and deaths. Another factor was the increase in the arithmetic mean of age of women at the birth of their first child. However, the development of social security in Poland has been influenced by the migration of refugees from Ukraine to Poland since 2022.